Impact of the COVID-19 Pandemic on Percutaneous Coronary Intervention in England: Insights From the British Cardiovascular Intervention Society PCI Database Cohort. (November 2020) - Kwok, Chun Shing; Gale, Chris P.; Curzen, Nick; de Belder, Mark A.; Ludman, Peter; Lüscher, Thomas F.; Kontopantelis, Evangelos; Roebuck, Chris; Denwood, Tom; Burton, Tony; Hains, Julian; Deanfield, John E.; et al.
Abstract : Background: The objective of the study was to evaluate changes in percutaneous coronary intervention (PCI) practice in England by analyzing procedural numbers, changes in the clinical presentation, and characteristics of patients and their clinical outcomes during the coronavirus disease 2019 (COVID-19) pandemic. Methods: We conducted a retrospective cohort study of all patients who underwent PCI in England between January 2017 and April 2020 in the British Cardiovascular Intervention Society database. Results: Forty-four hospitals reported PCI procedures for 126 491 patients. There were ≈700 procedures performed each week before the lockdown. After the March 23, 2020 lockdown (11th/12th week in 2020), there was a 49% fall in the number of PCI procedures after the 12th week in 2020. The decrease was greatest in PCI procedures performed for stable angina (66%), followed by non–ST-segment–elevation myocardial infarction (45%), and ST-segment–elevation myocardial infarction (33%). Patients after the lockdown were younger (64.5 versus 65.5 years, P <0.001) and less likely to have diabetes (20.4% versus 24.6%, P <0.001), hypertension (52.0% versus 56.8%, P =0.001), previous myocardial infarction (23.5% versus 26.7%, P =0.008), previous PCI (24.3% versus 28.3%, P =0.001), or previous coronary artery bypass graft (4.6% versus 7.2%, P <0.001) compared with before the lockdown. Conclusions: The lockdown in England has resulted in a significant decline in PCI procedures. Fewer patients underwent PCI for stable angina. This enabled greater capacity for urgent and emergency cases, and a reduced length of stay was seen for such patients. Significant changes in the characteristics of patients towards a lower risk phenotype were observed, particularly for non–ST-segment–elevation myocardial infarction, reflecting a more conservative approach to this cohort. Abstract : Supplemental Digital Content is available in the text.